Lire autour du littéraire pour lire la littérature - Riquois , Estelle (Neofilolog, 2022)
Reading literature in a foreign language can present several difficulties for learners. In order to facilitate this activity, we suggest using “literary documents” which help to prepare for reading and understanding and which help to develop students’ self-confidence. The objective is to establish reading skill in a foreign language through the transfer of strategies and the acquisition of contextual knowledge. Based on experiments carried out with several groups of students of French, we were able to observe greater autonomy and better understanding of the texts read.